Thiosulfinates Inhibit Platelet Aggregation and Microparticle Shedding at a Calpain-dependent Step - Rendu, Francine; Brohard-Bohn, Brigitte; Pain, Sabine; Bachelot-Loza, Christilla; Auger, Jacques (Thrombosis and Haemostasis, 2001)
Thiosulfinates (TSs) are sulfur compounds generated through the processing of different Allium species with antiplatelet property. To further define this platelet inhibitory effect we studied diallyl-TS (Al2TS), dipropyl-TS (Pr2TS), and dimethyl-TS (Me2TS) on platelet responses. The three TSs inhibited dose-dependent platelet aggregation, with IC50 values of 15 ± 2, 19 ± 2, and 9 ± 1 μM for Al2TS, Pr2TS and Me2TS, respectively. TSs had no effect on the expression of a platelet procoagulant surface, measured by flow cytometry as the binding of annexin V-FITC. They inhibited the microparticle shedding and clot retraction. Since the microparticle shedding is a calpain-activation dependent step, we assessed calpain activation by analysis of autoproteolysis in shorter active forms and by talin proteolysis in the presence of TSs. Calpain activation was inhibited by TSs independently of fibrinogen binding. Thus, TSs represent a new category of platelet inhibitors, acting on cal-pain-induced events.
Keywords: Allium; calpain; microparticles; platelet aggregation; talin